MENILAI PENGURUS GEREJA (MAJELIS) SESUAI KINERJA DALAM PELAYANAN MASING-MASING DENGAN MENGGUNAKAN METODE ASSIGNMENT PADA QM FOR WINDOWS - Wilson Simatupang; Yosia Suhendri Rajagukguk; Jhon Kristopel Manalu; Parapat Gultom (JURNAL ILMIAH RESEARCH STUDENT, 2026)
The management and performance evaluation of church administrators (church elders) are essential aspects of improving the effectiveness of ministry within the church. Performance assessments that are still conducted subjectively often result in inaccuracies when evaluating the suitability of responsibilities with each administrator's capabilities. This study aims to evaluate and determine the appropriate placement of church administrators based on their ministry performance using the Assignment method implemented through the QM for Windows application. The Assignment method is employed to optimize the allocation of church administrators to the most suitable ministry areas based on predetermined performance scores. This research adopts a quantitative approach by collecting performance data for each administrator according to several evaluation criteria, which are then processed using the Assignment feature in QM for Windows to obtain an optimal solution. The results indicate that the Assignment method is capable of providing objective and efficient recommendations for assigning church administrators, ensuring that each ministry area is staffed by individuals whose performance best matches the required responsibilities. Therefore, the implementation of this method can assist church leaders in making more accurate, transparent, and measurable decisions while enhancing the overall effectiveness of church ministry.